(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
For a polyatomic molecule, the classical partition function is obtained in a form that has a factor corresponding to the free translational motion of the atom for each atom in an effective volume determined by the average vibrational amplitudes of the atom and the geometrical arrangement of the neighboring atoms. For any choice of internal coordinates, a method is provided to measure the suitable volume components. Harmonic motions, internal rotations and reaction coordinates are used in the procedure. Quantum mechanical adjustments introduce external considerations for high-frequency vibrations that shrink the volume components.Since local properties largely characteristic of the bonds in the vicinity of each atom decide the key factors in this type of the partition function, several of these factors remain virtually constant and can be excluded in calculations comparing the reactants in a chemical reaction with the products or with the activated complex.